Pengaruh Religiusitas Terhadap Academic Integrity pada Remaja: Systematic Literature Review - Chelmidar, Syarah; Muslikah, Muslikah; Sutoyo, Anwar (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
Integrity and religiosity play a crucial role in shaping adolescents' academic behavior, particularly in preventing academic dishonesty. Integrity, as a fundamental attribute, supports the development of responsible and productive individuals, while religiosity enhances moral awareness and self-control. Academic dishonesty, including cheating and plagiarism, is an ethical violation that negatively impacts both individuals and educational institutions. Research indicates that higher levels of religiosity are negatively correlated with academic dishonesty because religious individuals tend to uphold moral and ethical values. However, other factors, such as academic pressure, also influence dishonest behavior. Therefore, a holistic approach that strengthens integrity, fosters religiosity, and manages academic stress is necessary to cultivate a generation of youth with high integrity who uphold ethical values in education. This study reviewed seven articles selected based on predetermined inclusion criteria. The databases used for article searches included ScienceDirect, Taylor & Francis, and Google Scholar. The findings reveal that religiosity plays a significant role in shaping the ethical attitudes and behaviors of adolescents. Individuals with a deep understanding of religion tend to avoid academic dishonesty due to their belief in a higher moral oversight. ___________________________________________________________________Integritas dan religiusitas memainkan peran penting dalam membentuk perilaku akademik remaja, terutama dalam mencegah kecurangan akademik. Integritas, sebagai atribut fundamental, mendukung pengembangan individu yang bertanggung jawab dan produktif, sementara religiusitas membantu meningkatkan kesadaran moral dan kontrol diri. Kecurangan akademik, seperti menyontek dan plagiarisme, merupakan pelanggaran etika yang berdampak negatif pada individu dan institusi pendidikan. Penelitian menunjukkan bahwa tingkat religiusitas yang tinggi berkorelasi negatif dengan kecurangan akademik, karena individu yang religius cenderung menghormati nilai-nilai moral dan etika. Namun, faktor lain seperti tekanan akademik juga memengaruhi perilaku curang. Oleh karena itu, pendekatan holistik yang mencakup penguatan integritas, peningkatan religiusitas, dan pengelolaan tekanan akademik diperlukan untuk menciptakan generasi muda yang berintegritas tinggi dan menjunjung nilai-nilai etis dalam pendidikan. Penelitian ini menggunakan 7 artikel yang ditelaah dengan inklusi yang telah ditentukan. Database yang digunakan untuk memudahkan pencarian artikel adalah Sciencedirect, Taylor & Francis, dan Google Scholar. Hasil dari penelitian ini menemukan bahwa religiusitas memainkan peran penting dalam membentuk sikap dan perilaku etis remaja. Individu dengan pemahaman agama yang mendalam cenderung menghindari kecurangan akademik karena percaya akan adanya pengawasan moral yang leìbih tinggi.